BONE HEALTH IN PARKINSONISM: A QUALITY IMPROVEMENT PROJECT. Issue 12 (15th November 2016) - Silvester, Lydia; Kobylecki, Christopher
Abstract : Introduction: Parkinson's disease (PD) and atypical parkinsonian disorders are independent risk factors for fracture. However, there are no specific national guidelines for patient management. We assessed 257 patients from tertiary movement disorder clinics using recently proposed guidelines1 in a quality improvement study. Methods: Fracture risk over ten years was estimated using QFracture, a validated risk assessment tool. 150 patients with PD and 107 with atypical parkinsonism were assessed. Risks were collated and reviewed with reference to proposed guidelines. Results: The mean ten year major osteoporotic fracture risk was 14.3% in PD and 23.8% in atypical parkinsonism; hip fracture risk was 10.4% for PD and 17% in atypical parkinsonism. According to proposed guidelines, over 50% of the cohort (77 atypical parkinsonism and 69 PD patients) could be considered for bone sparing therapy, whereas only 8% were receiving treatment. Discussion: We recommend systematic fracture risk assessment of patients with parkinsonism, as well as more thorough documentation to improve the accuracy of assessment. Since undertaking this work, we have made changes to practice which will facilitate more robust fracture risk assessment in patients with parkinsonian syndromes.